Analisis Minat Belajar Siswa Terhadap Pembelajaran Daring PJOK Selama Pandemi di SD Inpres Galangan Kapal II Makassar - Nurliani Nurliani; Hasbi Asyhari; Akbar Sudirman (Seminar Nasional LP2M UNM, 2021)
Abstract. Physical education is a subject with a lot of physcal activity such as running, throwing, hitting and jumping. During the covid 19 pandemic, learning is done online. With a different learning concept than before, it can affect students interest in learning, especially in physical education during the covid 19 pandemic. The type of research used is descriptive research. Population in this study were all students at SD Inpres Galangan Kapal II. The sample selected was 70 students of grade V SD Inpres Galangan Kapal II. The test instrument used in this study was a questionnaire. The results showed that students interest in learning about a physical education online during the covid 19 pandemic at SD Inpres Galangan Kapal II Makassar classified as high that is equal to 61%. Learning practices must be based on orientation to children based on a positive relationship that understands each other between teachers, students and parents. Teachers and parents can discuss about student learning, students habits at home, and the development of the student learning process. Teachers can create learning models and strategies by utilizing effectively packaged media that are easily accessible and understood by students.Keywords: Physical Education Online, Interest in Learning